Religious Moderation in Shaping Interfaith Relations: A Comparative Study of Indonesia and Malaysia - Hermawan, Ahmad; Matas, Jesus Alberto Valero (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This study aims to examine the role of religious moderation in shaping interfaith relations in Indonesia and Malaysia. The research investigates how state policies and community-based initiatives contribute to social harmony and interfaith cooperation. It also seeks to identify the challenges each country faces in promoting religious moderation and its impact on Muslim-Christian interactions. The research employs a qualitative comparative approach, incorporating in-depth interviews, participatory observations, and focus group discussions with religious leaders, government officials, and interfaith activists. Data collection was conducted in key regions with diverse religious populations, including Yogyakarta and Surabaya in Indonesia, as well as Kuala Lumpur and Selangor in Malaysia. Thematic analysis was used to identify patterns in religious moderation practices and their influence on interfaith harmony. The study finds that Malaysia’s religious moderation is actively supported by government policies, resulting in a more structured and dynamic interfaith environment. The National Unity Blueprint and other pluralism-oriented initiatives have contributed to stronger cooperation among religious communities. In contrast, Indonesia’s religious moderation efforts remain largely formal and symbolic, facing cultural resistance, particularly in rural areas. Limited local government support and socio-historical tensions further hinder effective interfaith engagement in Indonesia. The findings underscore the importance of government involvement in shaping interfaith harmony. The study suggests that Indonesia could benefit from adopting a more structured approach to religious moderation, integrating state-backed policies with grassroots engagement. The research also highlights the role of religious education and interfaith dialogue in reducing social tensions and fostering inclusive religious pluralism. This research contributes a novel comparative perspective on religious moderation by systematically analyzing policies and their social impact in two multicultural nations. Unlike previous studies that focus solely on qualitative descriptions, this study incorporates empirical insights into the effectiveness of religious moderation policies in fostering interfaith harmony. The findings provide valuable recommendations for policymakers and religious leaders in designing more effective pluralism strategies to enhance interfaith cooperation.